THE ECONOMIC POTENTIAL OF THE CRISIS (CONCEPTUAL APPROACH) - Ammar Neamah Awada; Anas Mahmood Ibrahim (Scholars Digest Publishing, 2023)
The Economic Potential Of The Crisis (Conceptual Approach) It is critical to take into account a country's anti-crisis capacity, taking into account the circumstances of its construction and application, as the technical structure of society and the existing concept of capitalist economic development cannot handle the current problems of the 21 century. Considering the adaptability of public administration, the technological capabilities of social production, as well as the human capacity to make complex decisions on the more effective combination of resources in light of the radical changes in the conditions that lead to the formation and attraction of anti-crisis potential, it is necessary to clarify this potential's essence. The system's ability to adjust to crisis situations and continue the trend of economic growth is provided by the development potential. The impact of crisis phenomena is affected by the anti-crisis potential (as an additional factor), which aids in overcoming the detrimental effect that has resulted in a severe fall in economic growth. The ability to attract additional resources during a crisis is a key aspect of the "crisis potential" concept, with the degree of adaptability of public administration, the technical capacity of social production, and the capacity of labor to make difficult decisions in the face of uncertainty all playing key roles. Anti-crisis potential is an opportunity that, via anti-crisis management, is transformed into a powerful tool for thwarting the occurrence of crises. The 2020 worldwide financial crisis, which was brought on by the coronavirus SARS-CoV-2, results in a considerable decline in GDP per capita in countries with robust economies (the USA, Austria, Germany, France, and Spain). In the meantime, several nations (such as China and Israel) have experienced further sustainable development while maintaining their current economic conditions. This pattern results from the fact that for some systems, the crisis not only poses a threat but also presents chances for the creation of novel resource combinations, which have a large economic impact and spur continued development. We can observe many trajectories if we study the responses of nations to and recovery from global crises. The phrase "economic potential of the global crisis" has been introduced because it has been demonstrated that several nations in the globe are strengthening their economies after economic crises. The likelihood of significant regional economic growth, the ability of the national economy to accomplish a strategic objective by utilizing shifts in the global market, and shifting places on the global stage are all examples of the economic potential of the crisis.
Keywords: regional development potential, economic crisis, GDP, anti-crisis potential.